Rural Poverty and Indebtedness : A Study in Three Thai Villages in Nongbua District, Nakhonsawan Province - Narkwiboonwong, Werachai (1995)
This study investigates the nature and characteristics of rural indebtedness and poverty in three selected villages in Thailand. The study reveals that the commercialization of agriculture increased farmers' investment costs for farming which were not necessary during the subsistence period. Their way of life also changed and tended to rely on the outside market for most things, even food which they used to produce themselves. The deforestation in the study areas had caused severe environmental degradation. Poor soil condition was the main factor contributing directly to low incomes, thus affecting the large number of poor in the villages. The commercialization of agriculture also pushed farmers to require credit. However, lack of land titles deterred many farmers from approaching institutional sources of credit, which provide loans with low interest rates. Many farmers were found to be indebted as a consequence of either production investments or consumption costs. The main reasons were high expenditure for both farm inputs and household consumption, and low yields caused by drought and pests. The main solution to poverty and indebtedness of farmers was to find additional work : non-farm and off-farm earnings. Factors associated with farmers indebtedness and poverty were: 1) political factors : government programmes; 2) economic factors : the lack of land or land title, credit accessibility, and price fluctuation; 3) physical factors: drought and pests, ecological degradation, and poor soil conditions; and, 4) personal attributes, such as gambling, extravagance, laziness, drinking and drug addiction. Suggestions to solve the problem of poverty and indebtedness are to apply the 'safety-first' principle by sustainable agriculture, such as agro forestry or integrated farming. To deal with risks of over supply and low prices, farmers, especially the poor, should be involved in several sub-enterprises and direct marketing. Finally, credit unions, cooperatives, and savings groups should be strengthened to ensure sustainable development of farmers in terms of self-reliance instead of having to rely on the capital of outsiders.